Clarifying Clinical Nurse Consultant work in Australia: A phenomenological study. Issue 4 (December 2015) - Cashin, Andrew; Stasa, Helen; Gullick, Janice; Conway, Rae; Cunich, Michelle; Buckley, Thomas
Summary: The Clinical Nurse Consultant role in Australia is an Advanced Practice Registered Nurse Role (APRN). This role has been conceptualized from the discrete pillars of research, education, practice, system support and leadership, articulated in the Strong Model of Advanced Practice. This conceptualization has been manifested in job descriptions, workforce planning and course design. This paper explored whether there was a more refined way of conceptualizing the unique 'value add' of the role. A hermeneutic phenomenological approach was employed to explore the lived experience of the role. It was identified that the pillars of education, practice, leadership and research are interconnected and expressed in the system work of the Clinical Nurse Consultant. The findings have implications for education and workforce planning.